Hepatocellular Carcinoma Intrinsic Cell Death Regulates Immune Response and Prognosis - De Re, Valli; Rossetto, Anna; Rosignoli, Alessandro; Muraro, Elena; Racanelli, Vito; Tornesello, Maria Lina; Zompicchiatti, Aron; Uzzau, Alessandro (Frontiers in Oncology, 2022)
Ablative and locoregional treatment options, such as radiofrequency, ethanol injection, microwave, and cryoablation, as well as irreversible electroporation, are effective therapies for early-stage hepatocellular carcinoma (HCC). Hepatocyte death caused by ablative procedures is known to increase the release of tumor-associated antigen, thus enhancing tumor immunogenicity. In addition, the heat ablative resection induces pyroptotic cell death accompanied by the release of several inflammatory factors and immune-related proteins, including damage-associated molecular patterns (DAMPs), heat shock proteins (HSPs), ficolin 3, ATP, and DNA/RNA, which potentiate the antitumoral immune response. Surgical approaches that enhance tumor necrosis and reduce hypoxia in the residual liver parenchyma have been shown to increase the disease-free survival rate by reducing the host’s immunosuppressive response. Scalpel devices and targeted surgical approach combined with immune-modulating drugs are an interesting and promising area to maximize therapeutic outcomes after HCC ablation.